The Influence of Culinary Quality and Café Atmosphere on Repurchase Intention: The Medition role of Consumer Satisfaction - Kurniawan, Sendy; Musprihadi, Ribut; Hasyim, Hasyim (Untag Business and Accounting Review, 2025)
This study aims to determine the effect of culinary quality and café atmosphere on repurchase intention, directly and indirectly through consumer satisfaction. The population used is all consumers who have made purchases at the Makan Minum Khu Mijen Semarang cafe, with a sample size of 85 respondents. The sampling technique used is accidental sampling. The data source used is primary data, with a data collection method using a questionnaire. The data analysis technique used is path analysis and the Sobel test. The results of the hypothesis test obtained that culinary quality has a positive and significant effect on consumer satisfaction, and café atmosphere has a positive and significant effect on consumer satisfaction. Culinary quality has a positive and significant effect on repurchase intention, café atmosphere has a positive and significant effect on repurchase intention, and consumer satisfaction has a positive and significant effect on repurchase intention. The results of the Sobel test show that consumer satisfaction can mediate the effect of culinary quality and café atmosphere on repurchase intention. The conclusion states that culinary quality and café atmosphere positively affect consumer satisfaction and repurchase intention. Managers should involve the variable of culinary quality in the promotion on social media marketing.